"Sharon"s" blood through Judges 11:31–40: The sacrificial lambs in African women"s lenses - Juma, Dorcas C. (HTS teologiese studies, 2023)
The rate at which women and girls have been ‘butchered’ in Africa before and during the COVID-19 pandemic suggests that violence against women in patriarchal settings is more tolerable. According to Exodus 21:12, Leviticus 24:17, Deuteronomy 12:312, 2 Kings 17:31 and Isaiah 66:3, murder and human sacrifice are an abomination and defile the land. Unfortunately, it is heartbreaking to note how the murder of women finds justification, as shown in Judges 11:31–40. Ironically, in Genesis 22:13, the sacrifice of Isaac is prevented through the provision of a sacrificial lamb. In this conversational platform, an African women’s hermeneutical lens to Judges 11:31–40 enables one to reimagine female bodies and motherhood as a theological phenomenon. It is proposed that ‘Sharon’s blood’ presents murdered women as Mother Earth’s sacrificial lambs of Africa, whose lives do not go unnoticed by God. Reimagining female bodies and motherhood as a theological phenomenon arguably enables the voices of murdered women to cry for justice from beyond the grave. If ‘the Sharons’ and their unborn babies do not receive justice, the ground continues to be defiled by human blood and remains ‘cursed’ (Mi 6:15). We will plant but not harvest; hence, there is a direct relationship between female bodies, motherhood and Mother Earth. One therefore asks: can scholarly conversational platforms enable murdered women of African descent to cry for justice from beyond the grave, allowing for life to flourish ‘again’?Contribution: This article contributed new knowledge to feminist studies by presenting murdered female victims of gender-based violence (GBV) as the sacrificial lambs of Mother Africa, whose innocent blood continues to cry for justice from beyond the grave. From an African hermeneutical lens, this research article reimagined female bodies and motherhood as a theological phenomenon in order to arguably enable the voices of murdered women to cry for justice from beyond the grave.